Just value of the Tactebel energy: an valuation from the main models of pricing asset - Campos, Renato (2010)
This study aimed to determine the current fair value of Tractebel Energia, from the main asset pricing models. The company was taken as the object due to its stable growth and the ease of obtaining data, since it is located in the city of Florianopolis. Nevertheless, the volatility in its shares has been priced aroused interest. Therefore, this study intended to provide subsidy for the decision making of investors regarding the purchase or sale of company stock. For this, the theoretical treat on the concept of asset valuation and the main models available, emphasizing their applications and limitations, which are: assessment book on, discounted dividend model and discounted cash flow. Regarding the methodological aspect, the research fits into exploratory, descriptive, highly quantitative field study and case. Moreover, it was made use of desk research, literature, interview and program Economática. Thus, the analysis of data initially sought to raise the assumptions demanded by each of the models surveyed ad apply them. The results were then compared and adjusted so that there is consistency. He was later adopted an arithmetic mean to assign a fair value to the company. From this average was defined as an acceptance range, depending on the variability of results and uncertainty in the estimates.